Experimental search of parametric X-ray radiation in a silicon crystal at a small angle near the velocity direction of relativistic electrons; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 173, iss. 1-2 : Radiation from Relativistic Electrons in Periodic Structures - Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Padalko D. A. Dmitry Andreevich; Potylitsyn A. P. Alexander Petrovich; Vnukov I. E. (2001, 2001)
Title screen